Bioethics for scientists - Bryant, J. A; Baggott La Velle, Linda; Searle, John R (Wiley & Sons, 2002)
A dictionary definition of Bioethics is, \'the ethics, or moral principles and rules of conduct, of medical and biological research\'. This book is an introductory text of just biological and not medical bioethics. It covers the ethics of experimentation, including genetic manipulation, in plants and animals; ethics and biodiversity, ethics and the environment. There is increasing interest in bioethics - both in academia and by the media and the general public. Awareness of bioethics is incorporated into Biological / Environmental Science courses, plus the first dedicated modular courses on bioethics are starting up. Includes case studies Has questions for students Chapters include environmental, animal, agricultural and reproductive ethics as well as a wide range of issues regarding genetic manipulation.
Keywords: etika, bioetika, lékařská etika; bioetika; Bioethics; humanitní vědy a umění